Walter Andrew Bell (1889-1969) Canadian Carboniferous Stratigrapher, Paleobotanist and Paleontologist par excellence - von Bitter, Peter (Geoscience Canada, 1997)
Summary Walter Andrew Bell (1889-1969) was a gentle, modest man of few words, born to Scottish Presbyterian parents in St.Thomas, Ontario. After graduating from Queen's and Yale universities, he began his full-time career with the Geological Survey of Canada (GSC) in 1920, progressing through the ranks from Assistant Palaeobotanist to Director. Bell was Director from 1950 to 1953, pivotal years in the emergence of the modern GSC, when he encouraged and strengthened paleontological and stratigraphie studies. Over his exceptionally long career Walter Bell authored or co-authored 70 publications, mostly concerning Carboniferous stratigraphy, paleobotany and paleontology of Atlantic Canada. He also contributed significantly to central and western Canadian Mesozoic and Cenozoic paleobotany.